RIBA DALAM PANDANGAN AL-QUR’AN DAN HADIST - Muhammad Alyaafi; Muhammad Raffi Andhera (Jurnal Sosial Humaniora Sigli, 2023)
Riba, as the practice of adding or taking additional money in money lending transactions, is an important concern in Islamic law. In the Al-Qur'an and Hadith, usury is expressly prohibited and is considered a major sin that must be avoided by Muslims. The background to this problem involves historical aspects, where the practice of usury became a concern at the time of the Prophet Muhammad SAW and required decisive action. The practice of usury violates the principles of justice and can reinforce social inequalities and economic imbalances. In the era of the modern financial system, the practice of usury also affects the global financial sector, presenting a dilemma for Muslims who want to implement Islamic economic principles. Therefore, a deep understanding of the views of the Qur'an and Hadith regarding usury is important in developing an economic system that is just and in accordance with Islamic teachings. This study aims to analyze the prohibition of usury in the Qur'an and Hadith and its implications in the context of Islamic economics. Through a detailed analysis of relevant verses of the Qur'an and hadiths, a deep understanding of the concept of usury, its impact on society, and applicable Islamic economic alternatives is presented. Thus, this research provides a better understanding of usury in the view of the Qur'an and Hadith, so that it can encourage critical thinking and concrete solutions in carrying out economic activities in accordance with Islamic teachings.Keywords : Riba, Al-quran, Hadits.